How Multilingual Policies Can Fail: Language Politics Among Ethiopian Political Parties - Worku, Mehari Zemelak (My University, 2018)
Because language has instrumental as well as symbolic values, the issue of language will always have a political aspect (Smith 2008). Often, the choice of language and its use is construed as one of the central traits to people’s definition of themselves. Besides, any given state must decide or determine the language that it deems appropriate to carry out its development and to generate, disseminate and enrich the knowledge necessary for such development. However, the case grows problematic when it comes to Sub-Saharan Africa where “every language carries a distinct and weighty baggage” of identity (Obeng & Purvis 1999). The decision was not easy for different regimes in Ethiopia, home of more than 80 ethnic groups (CSA 2008). The three consecutive regimes which have ruled the country for the last 75 years followed different paths in addressing this diversity management question. The reframing of the country under ethnic federalism, which legislates Amharic as the working language of the federal government (hereafter WL) and guarantees the right of each ethnic state to decide its own WL, is the recent attempt to respond to the same politics of recognition. However, dissatisfied voices regarding the current language policy (hereafter LP) can still be heard among political groups. Some see it as ‘not enough’ while others see it as Balkanization. Despite a few research efforts and publications on the LPs of the consecutive governments of Ethiopia, there has been no research done on the alternative policies and options available among the political parties or their relative value as LPs. Thus, the grand objective of this study is to survey, analyze and evaluate the linguistic proposals of Ethiopian political parties in government, education, and endangered languages.
Keywords: Ethiopa; language policy; language politics